2021
DOI: 10.3390/biom11111612
|View full text |Cite
|
Sign up to set email alerts
|

Independent Clinical Validation of the Automated Ki67 Scoring Guideline from the International Ki67 in Breast Cancer Working Group

Abstract: Ki67 is an important biomarker with prognostic and potential predictive value in breast cancer. However, the lack of standardization hinders its clinical applicability. In this study, we aimed to investigate the reproducibility among pathologists following the guidelines of the International Ki67 in Breast Cancer Working Group (IKWG) for Ki67 scoring and to evaluate the prognostic potential of this platform in an independent cohort. Four algorithms were independently built by four pathologists based on our stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
(34 reference statements)
1
11
0
1
Order By: Relevance
“…Based on the consensus guidance of the 2011 St Gallen Conference, Ki-67 has been recommended not only as 1 of the classification criteria for Luminal breast cancer, but holds a promising role in the prediction of animation prognosis of multiple malignancies. [ 38 ] Tracing past research experience, the cutoff value for Ki-67 was set as 14% in this study to further explore its intrinsic interaction with disease prognosis. Unlike pT and pN, Ki-67 level presented significant independent prognosis in the regression analysis of influencing factors.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the consensus guidance of the 2011 St Gallen Conference, Ki-67 has been recommended not only as 1 of the classification criteria for Luminal breast cancer, but holds a promising role in the prediction of animation prognosis of multiple malignancies. [ 38 ] Tracing past research experience, the cutoff value for Ki-67 was set as 14% in this study to further explore its intrinsic interaction with disease prognosis. Unlike pT and pN, Ki-67 level presented significant independent prognosis in the regression analysis of influencing factors.…”
Section: Discussionmentioning
confidence: 99%
“…Manual preparation and editing of these images to achieve good results with automated counting would be too time consuming in our case. On the other hand, some groups have reported good results, some of them with free and open-source software, such as QuPath and ImageJ (Feng et al, 2020;Boyaci et al, 2021), but there is still room for improvement, both in free and commercial software (Vesterinen et al, 2022). This is an active field of research and, hopefully, the results may allow for full automatization of the positive cell counting in the future.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study assessed the reproducibility of QuPath to determine Ki-67 scoring following IKWG guidelines in a cohort of 157 patients with ER-positive breast cancer 71 Results found high inter-observer reproducibility between the 4 different algorithms developed and the reference standard (obtained by a separate QuPath algorithm on a subset of 30 patients) with an ICC of 0.938 (95% CI, 0.920 to 0.952). 71 A prior study examining the Ki-67 scoring using the QuPath platform found similar results. 72 The April 2022 American Society of Clinical Oncology (ASCO) guidelines update notes that there were analytical differences in the way that Ki-67 was measured in the monarchE trial compared to the recommendations made by the IKWG.…”
Section: Discussionmentioning
confidence: 99%